C-Conformal Transformation of Berwald and Cartan Connection of Randers Space - M.Ajith Rao, Ramesh Kumar T H (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this article, we consider the Randers metric and we proved that it is a weakly Berwald metric. Further, we show that, the difference tensor corresponding to the Cartan and Berwald connections are invariant under C- conformal transformation.